Challenges in using Electrocoagulation Process in Removal of Nickel Metal in Wastewater: a Literature Review - Muhammad Ghozali Harahap; Muhammad Sonny Abfertiawan; Mindriany Syafila (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
In recent years, the surge in nickel production, driven by the growing demand for electric vehicle batteries, has raised concerns regarding environmental consequences. The nickel mining and processing industries contribute to increased nickel levels in wastewater, presenting a serious threat to aquatic ecosystems and human health. This article emphasizes the urgency of developing effective technologies for treating nickel-contaminated wastewater. Electrocoagulation emerges as a promising method, providing high efficiency, minimal sludge production, and cost-effectiveness. The article critically and systematically reviews the potential of the electrocoagulation process in nickel removal from wastewater. In the review, we identify and analyze nearly 32 studies published from 2013 to 2023. We discuss contaminant removal mechanisms and analyze trends in the use of operational parameters. This article identifies the most commonly applied conditions: aluminum electrodes, inter-electrode spacing ≥ 1 cm, current density ≤ 10 mA/cm², initial pH 6 ≤ pH < 11, electrolysis time < 60 min, batch operation, and initial nickel concentration > 50 mg/L. This comprehensive review serves as a foundational resource for advancing electrocoagulation technology in the removal of heavy metals from nickel wastewater.